IMF Staff Papers Supplement. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1984)
Only references are in the PDF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet